1997
DOI: 10.1089/cbr.1997.12.19
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis of Tumor Cells Induced by Substances of the Circulatory System

Abstract: Despite global abnormalities of the immune system, such as in AIDS, the incidence of only a few kinds of tumor increases, and even in the development of these tumors the degree of immunosuppression seems not to be a critical factor. This means that the known immune system has no significant role in the tumor preventing mechanism. Thus, the fact that tumors do not develop in the majority of the population during their lifetime, indicates the existence of an additional defense mechanism of the immune system. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 18 publications
1
8
0
Order By: Relevance
“…41 Finally, it was reported earlier that many substances of PADS, namely ascorbic acid, 56,57 arginine, 58 2-deoxy-D-ribose, 59 mannose, 60 orotic acid, 61 pyridoxine, 62 riboflavin, 63 and tyrosine, 64 had antitumor effect when they were used singly. Taking our experimental findings into account that the above substances, moreover, could increase the effect of each other on tumor cells synergistically, [37][38][39][40] the above observations about the effect of the same substances singly strongly support the existence of the PADS and corroborate our results.…”
Section: Survival Time (Days)supporting
confidence: 87%
See 3 more Smart Citations
“…41 Finally, it was reported earlier that many substances of PADS, namely ascorbic acid, 56,57 arginine, 58 2-deoxy-D-ribose, 59 mannose, 60 orotic acid, 61 pyridoxine, 62 riboflavin, 63 and tyrosine, 64 had antitumor effect when they were used singly. Taking our experimental findings into account that the above substances, moreover, could increase the effect of each other on tumor cells synergistically, [37][38][39][40] the above observations about the effect of the same substances singly strongly support the existence of the PADS and corroborate our results.…”
Section: Survival Time (Days)supporting
confidence: 87%
“…L-ascorbate was highly toxic in vitro even when it was applied individually at a high concentration as its maximum concentration in the serum; therefore, we determined its nontoxic amount, and this was used in the maximal active mixture. The 2-deoxy-D-ribose, which was a component of active mixture in the previous experiments, [37][38][39][40] was omitted from the active mixture because we could not find data about its serum concentration in the special literature. The cells were counted when the untreated cells proliferated to approximately 5 3 10 5 .…”
Section: Comparison Of the Effects Of Active Mixtures Containing Theimentioning
confidence: 99%
See 2 more Smart Citations
“…We have shown earlier that the AM, but not the individual components induced apoptosis of tumor cell lines 19. Here we showed that the AM is capable to inhibit the growth of a wide range of murine and human tumors, induces apoptosis of PC‐3 human prostate carcinoma cells in vitro , and increases the number of apoptotic cells in PC‐3 xenografts.…”
Section: Discussionmentioning
confidence: 53%